Women who become men? The sworn virgins in Albanian traditional culture - Donato Martucci (Anuac, 2015)
Between the end of the nineteenth century and the first half of the twentieth, many travelers and scholars who traveled in the mountainous areas of Western Balkans Dinaric Alps were fascinated by the presence of women who looked, in varying degrees, masculinized: the sworn virgins or virgjineshë. The descriptions of the phenomenon, however, were often influenced by the observer's eye, alien to the socio-cultural context. This essay will explore the historical and ethnographic evidences of this phenomenon, reconstructing the transformations and discussing the category of “social man”, associated with the sworn virgins.